Globalizing American studies - Edwards, Brian T., 1968-; Gaonkar, Dilip Parameshwar, 1945- (University of Chicago Press, 2010)
The discipline of American studies was established in the early days of World War II and drew on the myth of American exceptionalism. Now that the so-called American Century has come to an end, what would a truly globalized version of American studies look like? Brian T. Edwards and Dilip Parameshwar Gaonkar offer a new standard for the field's transnational aspiration with Globalizing American Studies . The essays here offer a comparative, multilingual, or multisited approach to ideas and representations of America.